Impact of sex and reproductive status on memory circuitry structure and function in early midlife using structural covariance analysis. Issue 4 (12th December 2018) - Seitz, Johanna; Kubicki, Marek; Jacobs, Emily G.; Cherkerzian, Sara; Weiss, Blair K.; Papadimitriou, George; Mouradian, Palig; Buka, Stephen; Goldstein, Jill M.; Makris, Nikos
Abstract: Research on age‐related memory alterations traditionally targets individuals aged ≥65 years. However, recent studies emphasize the importance of early aging processes. We therefore aimed to characterize variation in brain gray matter structure in early midlife as a function of sex and menopausal status. Subjects included 94 women (33 premenopausal, 29 perimenopausal, and 32 postmenopausal) and 99 demographically comparable men from the New England Family Study. Subjects were scanned with a high‐resolution T1 sequence on a 3 T whole body scanner. Sex and reproductive‐dependent structural differences were evaluated using Box's M test and analysis of covariances (ANCOVAs) for gray matter volumes. Brain regions of interest included dorsolateral prefrontal cortex (DLPFC), inferior parietal lobule (iPAR), anterior cingulate cortex (ACC), hippocampus (HIPP), and parahippocampus. While we observed expected significant sex differences in volume of hippocampus with women of all groups having higher volumes than men relative to cerebrum size, we also found significant differences in the covariance matrices of perimenopausal women compared with postmenopausal women. Associations between ACC and HIPP/iPAR/DLPFC were higher in postmenopausal women and correlated with better memory performance. Findings in this study underscore the importance of sex and reproductive status in early midlife for understanding memory function with aging.